Pharmacogenetics of Metformin Transporters Suggests No Association with Therapeutic Inefficacy among Diabetes Type 2 Mexican Patients - Adiel Ortega-Ayala; Nidia Samara Rodríguez-Rivera; Fernando de Andrés; Adrián LLerena; Eliseo Pérez-Silva; Adriana Guadalupe Espinosa-Sánchez; Juan Arcadio Molina-Guarneros (MDPI AG, 2022)
Mexico has been under official epidemiological alert due to diabetes since 2016. This study presents new information on the frequency and variants of metformin transporters OCT1, OCT2, OCT3, ABCB1, and CYP2C9 variants as well. It also reports the association with HbA1c control on 103 DMT2 patients. They were genotyped through real-time PCR (TaqMan assays) and grouped according to treatment: metformin and metformin + glibenclamide. Metformin plasmatic levels were determined through mass spectrometry. The analysis of HbA1c showed statistical significance across genotypes in polymorphisms rs72552763 (p = 0.022), rs622342 (p = 0.009), rs1128503 (p = 0.021), and rs2032582 (p = 0.009) within the monotherapy group. Bivariate analysis found no association between any polymorphism and HbA1c control. Two logistic regression models accounted for two diplotypes in OCT1 and ABCB1, including statistically significant covariates. The first model yielded significance in age (p = 0.026), treatment period [p = 0.001], BMI ≥ 25 kg/m2 (p = 0.043), and combined therapy (p < 0.001). There was no association with GAT/GAT of rs72552763 or A/A rs622342 in OCT1. The second model yielded significance in age (p = 0.017), treatment period (p = 0.001), BMI ≥ 25 kg/m2 (p = 0.042), and combined therapy (p < 0.001), finding no association with C/C of rs1128503 or G/G of rs2032582 in ABCB1. Our multinomial logistic regression results may benefit future predictive analyses in diabetic populations.